Strategi Pengembangan Desa Wisata Mukapayung Kabupaten Bandung Barat - Wilda Nabiyah; Dewi Rahmi (Bandung Conference Series: Economics Studies, 2024)
Abstract. The tourism sector is a sector that has the potential to be developed as a source of regional income with tourism development carried out by the government with the aim of improving the welfare of the community and the country. The qualitative research method used data collection techniques, namely observation, interviews, documentation and using SWOT analysis as an analysis method to determine the strongest strategy for developing the Mukapayung tourist village. Based on the research results, it was found that the strength of Wista Mukapayung Village is that it has a beautiful natural panorama, is located in a mountainous area, has fertile natural potential and is suitable for agrotourism development, has additional attractions in the form of a games arena, has a tourism awareness group organization (Pokdarwis), and has attractions. culture and education. Furthermore, the biggest opportunity for the Mukapayung tourist village is a form of program to increase economic development in rural areas, to become a form of program to preserve local nature, to get support from the local government in developing local tourism and to have the number of tourist visits which always increases every year. Abstrak. Sektor pariwisata merupakan sektor yang potensial untuk dikembangkan sebagai salah satu sumber pendapatan daerah dengan pembangunan pariwisata yang dilakukan pemerintah memiliki tujuan untuk mensejahterakan masyarakat dan negara. Metode penelitian kualitatif dengan teknik pengumpulan data yang dilakukan yaitu observasi, wawancara, dokumentasi dan menggunakan analisis SWOT sebagai metode analisis untuk menentukan strategi yang paling kuat untuk pengembangan desa wisata Mukapayung. Berdasarkan hasil penelitian ditemukan bahwa kekuatan Desa Wista Mukapayung memiliki keindahan panorama alam yang berpotensi, berlokasi di daerah pegunungan, potensi alam yang subur dan cocok untuk pengembangan agrowisata, memiliki atraksi tambahan berupa arena permainan, memiliki organisasi kelompok sadar wisata (Pokdarwis), dan memiliki atraksi budaya dan edukasi. Selanjutnya, peluang terbesar dari Desa wisata Mukapayung salah satu bentuk program untuk meningkatkan pembangunan perekonomian di daerah pedesaan, menjadi salah satu bentuk program untuk melestarikan alam setempat, mendapatkan dukungan dari pemerintah daerah dalam pengembangan pariwisata lokal dan memiliki jumlah kunjungan wisatawan yang selalu meningkat pertahunnya.